2014
DOI: 10.1177/1045389x14546779
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical investigation of ionic polymer transducers in shear sensing

Abstract: Ionic polymer transducers (IPTs), sometimes referred to as ionic polymer metal composites, are ionomers that are plated with conductive media such as metals enabling both actuation and sensing behavior. As sensors they are most often studied in bending mode; however, a measurable signal can be generated in any mode of mechanical deformation. The fundamental physical mechanism responsible for IPT sensing is an open topic. This report asserts that a reasonable mechanistic model should be able to explain IPT sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Furthermore, since the electrical conductivity of the solution inside the Nafion depends on the species present in the ionomeric channels, the resistivity of the IPMC is also affected and, consequently, the resistive-capacitive response of the device. Some authors found that the capacitive properties mainly dominate the electromechanical response of IPMCs [31][32][33] .…”
Section: Electromechanical Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, since the electrical conductivity of the solution inside the Nafion depends on the species present in the ionomeric channels, the resistivity of the IPMC is also affected and, consequently, the resistive-capacitive response of the device. Some authors found that the capacitive properties mainly dominate the electromechanical response of IPMCs [31][32][33] .…”
Section: Electromechanical Responsementioning
confidence: 99%
“…Bonomo et al 34 developed a circuit model to describe the IPMC electrical behavior, explaining that the electric charge accumulation causes the device flexural motions at the anode after an electrical potential is applied. Kocer et al 32 that the primary influence of the capacitive component of IPMC is related to its mechanical response. The stored electrical charge (Q) in the device after voltage application can be calculated by integrating the electric current as a function of time.…”
Section: Electromechanical Responsementioning
confidence: 99%
“…Variability and inconsistency, in turn, demand extensive property and performance characterization of each individual IPMC sample before use in any sensor system. Furthermore, until recent advancements [19][20][21][22], the limited understanding of the fundamental nature of material response to non-bending deformation in IPMCs has effectively precluded major breakthroughs in the development of non-bending mode sensors. In particular, a theoretical explanation of the compression sensing mode (electrical transduction of deformation in the thickness direction due to applied pressure normal to the electrodes) was only offered in 2017 in [22] and therein attributed to inhomogeneous strain through the IPMC thickness.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is manifested through a short circuit current that is a function of the imposed displacement, modulated by strain magnitude and rate. The effectiveness of IPMCs in compression sensing has been formerly investigated in [48] and recently established in [49], opening the door for new, multimodal sensing applications combining traditional benders with shear and compression sensors [50,51].…”
Section: Introductionmentioning
confidence: 99%